2021
DOI: 10.1097/ccm.0000000000005263
|View full text |Cite
|
Sign up to set email alerts
|

Effect of IV High-Dose Vitamin C on Mortality in Patients With Sepsis: A Systematic Review and Meta-Analysis of Randomized Controlled Trials*

Abstract: OBJECTIVES: The aim of this study was to conduct a systematic review and meta-analysis of randomized controlled trials to investigate whether IV high-dose vitamin C improves the short-term mortality of patients with sepsis. DESIGN: This study is a systematic review and meta-analysis of randomized controlled trials. We searched EMBASE, the Cochrane Central Register of Controlled Trials, and MEDLINE for randomized controlled trials that met inclusion crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
34
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 37 publications
4
34
0
2
Order By: Relevance
“…However, there are only 9 RCTs presenting time to intervention initiation in our meta-analysis, resulting in difficulty in judgement the effect of initiation time. Recent meta-analyses [11,13,[41][42][43]] also failed to find improved mortality among patients with sepsis, no matter combined therapy or monotherapy. Different inclusion criterion, duration, patient populations and timing of administration explain the heterogeneity of different research results to some extent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are only 9 RCTs presenting time to intervention initiation in our meta-analysis, resulting in difficulty in judgement the effect of initiation time. Recent meta-analyses [11,13,[41][42][43]] also failed to find improved mortality among patients with sepsis, no matter combined therapy or monotherapy. Different inclusion criterion, duration, patient populations and timing of administration explain the heterogeneity of different research results to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…The Surviving Sepsis Campaign of 2021: International Guidelines for Management of Sepsis and Septic Shock suggest IVVC for patients with sepsis or septic shock was not recommended, only as a weak recommendation according to the low quality of evidence [12]. Although systematic reviews and meta-analyses discussing IVVC in patients with sepsis were recently published [11,13,14], these studies did not include the newer randomized controlled trials (RCTs) [15][16][17] with a larger population of patients to provide better evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin C has been suggested as a possible therapy that attenuates the pathophysiology of sepsis [2]. Multiple randomized controlled trials (RCTs) addressing effectiveness and safety of vitamin C have reported varied conclusions [3]. Previously, published meta-analysis were limited by the sample size and highlighted the need of further studies with a larger number of patients to provide further evidence [3].…”
mentioning
confidence: 99%
“…Multiple randomized controlled trials (RCTs) addressing effectiveness and safety of vitamin C have reported varied conclusions [3]. Previously, published meta-analysis were limited by the sample size and highlighted the need of further studies with a larger number of patients to provide further evidence [3]. The recent publication of results from LOVIT (Lessening Organ Dysfunction with Vitamin C), the largest trial to date addressing this question, justifies re-examination of the evidence [4].PubMed and Scopus databases were searched for relevant studies by two investigators (MAT, UA) using the following keywords: "ascorbic, " "Vitamin C, " "ascorbic acid, " "sepsis, " "septic shock. "…”
mentioning
confidence: 99%
See 1 more Smart Citation